COVID‐19 and dermatology: a comprehensive guide for dermatologists. (10th June 2020) - Fahmy, D.H.; El‐Amawy, H.S.; El‐Samongy, M.A.; Fouda, A.A.; Soliman, S.H.; El‐Kady, A.; Farnetani, F.; Conti, A.; Zoeir, A.; Eissa, A.; Eissa, R.; Puliatti, S.; et al.
Abstract : Linked articles: COVID‐19 SPECIAL FORUM. J Eur Acad Dermatol Venereol 2020; 34: e291–e310 .